Cervicovaginal cytology and colposcopy evaluation as diagnostic methods of cervical intraepithelial neoplasia - Cabrera Paz, Jorge (2015)
OBJETIVE: To evaluate the specificity, sensitivity and positive predictive value of screening for cervical intraepithelial neoplasia (CIN) - Pap smear and colposcopy. compar'sndolas with the final diagnosis, given by the Pathology. DESIGN: Observational Research retrospect. LOCATION: Department of Obstetrics and Gynecology, Regional Hospital of Trujillo, January 1994 to April 1997. Material and metods: Review of medical records file Hospital 109 cases of positive cytology and colposcopy 107 cases who had histopathology. RESULTS: The Pap smear, has specificity 50%, sensitivity 80%, with a false positive proportion of 50% and 20% false negatives. Colposcopy has sensitivity 79%, specificity 25%, with a false positive proportion of 75% and 21% false negatives. The positive predictive values for cytology and colposcopy were 58% and 46% respectively. Conclusions: The Pap smear showed little value as a highly specific test for mass screening of CIN, while colposcopy presents adequate sensitivity; you can not establish the reliability when cytology is complemented by colposcopy